MEDIA LITERACY AND CYBERSECURITY - Xayitbayeva Roxila Juraboyevna (Bright Mind Publishing, 2026)
This abstract reveals the essence and importance of media literacy and cybersecurity in the modern information society. Media literacy contributes to the formation of personal skills for searching, analyzing, evaluating and consciously using information. Cybersecurity ensures the protection of personal data, information systems and digital resources from various threats. The abstract discusses the issues of safe use of the Internet, identification of false information, protection of personal data and the formation of information culture. This topic is important for young people and professionals, as it contributes to ensuring information security and the formation of responsible behavior in the media space.
Keywords: Media literacy, cybersecurity, information security, internet safety, digital technologies, information culture, personal data protection, information threats, misinformation, digital environment.